Assessing the short-term impacts of COVID-19 on Ethiopia’s economy: External and domestic shocks and pace of recovery - Aragie, Emerta A.; Taffesse, Alemayehu Seyoum; Thurlow, James (International Food Policy Research Institute, 2020)
In this paper, we analyze the economic impacts of response measures adopted in Ethiopia to curtail the spread of the COVID-19 pandemic. We carry out simulations using an economywide multiplier model based on a 2017 Social Accounting Matrix (SAM) for the country that properly depicts interactions between economic agents. The pandemic’s impact on the global economy combined with disruptions it causes in Ethiopia represents a large, unprecedented shock to the country’s economy. In such situations, a SAM-based multiplier model provides an ideal tool for measuring the short-term direct and indirect impacts of a shock on an economic system since there is limited room for proper adjustment of economic decisions. We model the seven-week partial lockdown policy implemented in Ethiopia from mid-March to early May 2020. We also consider two possible economic recovery scenarios that may emerge as the COVID-19 control policies are relaxed during the latter part of 2020 in order to generate insights on the potential continuing impact of the virus at the end of 2020. Although the country took early swift measures, our assessment of the partial lockdown measures suggests that they were not as strict as those observed in other Africa countries. Accordingly, our estimates of the economic costs of COVID-19 on Ethiopia are significantly lower than those reported for other countries on the continent. We estimate that during the lockdown period Ethiopia’s GDP suffered a 14 percent loss (43.5 billion Birr or 1.9 billion USD) compared to a no-COVID case over the same period. Nearly two-thirds of the losses were in the services sector. Although no direct restrictions were imposed on the agriculture sector, which serves as the primary means of livelihood for most Ethiopians, the sector faced a 4.7 percent loss in output due to its linkages with the rest of the economy. Poor export performance due to a slowdown in global trade and restrictions on the transport sector also partly explain the decline in agricultural output. The broader agri-food system also was affected considerably because of its linkages with the rest of the economy. In terms of the welfare of Ethiopians, we estimate that the economic impacts during the lockdown caused 10.1 million additional people to fall below the poverty line. These findings have implications for better understanding the direct and indirect impacts of COVID-19 and for policy design during the recovery period to return Ethiopia’s economy to a normal growth trajectory and to protect the livelihoods of the most vulnerable in the process.